Maintaining social support while social distancing: The longitudinal benefit of basic psychological needs for symptoms of anxiety during the COVID‐19 outbreak. Issue 6 (31st March 2022) - Costa, Sebastiano; Canale, Natale; Mioni, Giovanna; Cellini, Nicola
Abstract: Although social distancing measures could be potentially perceived as thwarting conditions for basic psychological needs and thus causing psychological distress, off(on)line social support could compensate for this frustration by providing psychological proximity. Using self‐determination theory, in this study, we aimed (a) to evaluate the change of perception in need satisfaction over time (before and during home‐confinement and after a month of lockdown) and (b) to test the short‐term longitudinal association between off(on)line social support, basic needs, and anxiety during social distancing measures in response to the COVID‐19 outbreak. During the lockdown period decreed by Italy in March 2019 to confront the COVID‐19 emergency, 1344 participants completed an online questionnaire and 131 participants completed a follow‐up after 1 month. Results showed a decrease in need satisfaction during home confinement and a further reduction after a month of lockdown. Cross‐sectional path analysis showed that both online and offline social support were associated with higher need satisfaction, which, in turn, was related to a lower level of anxiety. Longitudinal paths also confirmed the association between need satisfaction and anxiety. Collectively, these results suggest that maintaining psychological proximity despite social distancing measures may provide important avenues for reducing negative outcomes during forced home confinement.